Cocaine Abstinence and Reduced Use Associated With Lowered Marker of Endothelial Dysfunction in African Americans. Issue 4 (July 2015) - Lai, Hong; Stitzer, Maxine; Treisman, Glenn; Moore, Richard; Brinker, Jeffrey; Gerstenblith, Gary; Kickler, Thomas S.; Li, Ji; Chen, Shaoguang; Fishman, Elliot; Lai, Shenghan
<x xml:space="preserve">Abstract</x> Objectives: Clinical and epidemiological evidence suggests that cocaine use is associated with an increased risk of premature atherosclerosis. The objectives of this study were to explore (1) whether cocaine abstinence is associated with a reduced marker of endothelial dysfunction, (2) whether cocaine abstinence is associated with a slower coronary plaque progression, and (3) whether reduction in cocaine use is associated with a reduced marker of endothelial dysfunction in African American chronic cocaine users with contrast-enhanced coronary CT angiography-confirmed less than 50% coronary stenosis. Methods: Between March and June 2014, a total of 57 African American cocaine users with contrast-enhanced CT angiography-confirmed less than 50% coronary stenosis in Baltimore, Maryland, were enrolled in a 6-month follow-up study to investigate whether cocaine abstinence or reduction in cocaine use is associated with decreased endothelin-1 (ET-1) levels and coronary plaque progression at the 6-month follow-up. A voucher-based incentive approach was used to systematically reinforce cocaine abstinence, and urine benzoylecgonine test was implemented to confirm cocaine use. Results: Among the 57 participants, 44 were HIV-infected. The median of duration of cocaine use was 18 (interquartile range, 7–30) years. According to generalized estimating equation analyses, both cocaine abstinence and reduction in cocaine use in the 6 months were independently associated with decreased ET-1. The incidence of coronary plaque progression was 7.4/100 person-years and 23.1/100 person-years in those who were totally abstinent from cocaine and those who continued to use cocaine, respectively. However, the difference in the incidence between these 2 groups was not significant (exact P = 0.30). Conclusions: The findings of this study revealed a possible association of cocaine abstinence/reduction with lowered ET levels, which suggests that such changes in cocaine use might be beneficial for preventing endothelial damage. Further studies should be conducted to investigate whether ET-1 could be used as a marker for cocaine abstinence and reduction in cocaine use.